Electrical and spectroscopic characteristics of B2O3–Bi2O3–Al2O3–MgO glasses alloyed with MnO. (November 2022) - Priya, G. Krishna; Yusub, S.; Babu, A. Ramesh; Ram, N. Sree; Aruna, V.
Abstract: In this study, the dielectric properties, electron spin resonance (ESR), optical absorption spectra, emission spectra, Raman spectra, X-ray diffraction (XRD), and Fourier transform infrared spectra were determined for the glass network 65B2 O3 –20Bi2 O3 –10Al2 O3 -(5-x)MgO-xMnO (0 ≤ x ≤ 1 mol%). The glass system was prepared by using the melt quenching and heat treatment process. Dielectric parameters were evaluated for the glasses in the broad frequency range (10 3 –10 6 Hz), and the parameters indicated increases in the semiconducting nature of the glasses. ESR and emission spectra obtained for the samples demonstrated the presence of manganese ions in the divalent state. The optical absorption spectra contained bands due to Mn 2+ ions. The optical band gap (Eg ) and Urbach energy (ΔE) values were calculated for the samples. The Eg value decreased as the MnO concentration increased whereas the ΔE value tended to decrease, thereby suggesting a gradual decrease in the strength of the glasses. The amorphous properties of the glasses were demonstrated by the XRD spectra. The spectroscopic and dielectric analyses indicated the depolymerization of the glasses. Graphical abstract: Melt quenching and heat treatment technique was used in fabricating the glass system 65B2 O3 –20Bi2 O3 –10Al2 O3 -(5-x)MgO-xMnO with 0 ≤ x ≤ 1 mol% (x = 0, 0.2, 0.4, 0.6, 0.8 and 1). The amorphous nature of glasses was authenticated by X-ray diffraction. Optical absorption spectra of the specimens were investigated in the wavelength range 350–600 nm. These absorption spectra evinced the bands owing to Mn 2+ ions engaging the octahedral positions. The direct and indirect band gap of the samples was evaluated. A decrease in the energy band gap indicates an increase in semiconducting nature of glasses. ESR spectra displayed the hyperfine structure of the samples. FTIR and Raman spectra of the specimens were investigated. A continuous decrease in the values of dielectric breakdown strength and activation energy for conduction of glasses is detected. All reports approved the increasing semiconducting nature of glasses. Image 1 Highlights: The physical parameters of B2 O3 –Bi2 O3 –Al2 O3 –MgO: MnO glasses were estimated. Optical absorption spectra exhibited a prominent band at 480 nm due to Mn 2+ ions. FTIR and Raman spectra of glasses espied the traditional bands due to borate units. ESR and Emission spectra supported the existence of Mn 2+ ions in the glasses. Dielectric break down strength of the specimens were computed.